Impact of educational financing on the social mobility of university graduates: An analysis using regression discontinuities; Impacto del financiamiento educativo en la movilidad social de graduados universitarios - Patricia Hernández Medina; Gabriel Ramírez Torres; Diego E. Pinilla; Luis Morales (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
The aim of this research was to evaluate the impact of the financial aid programme at a private university in Venezuela on the outcome variables of post-graduation or social mobility, such as remuneration at the time of graduation and at present, and the probability of entering the labour market. We used the fuzzy regression design for multiple treatments, given that the programme consists of the application of percentage discounts on tuition, where the allocation index only shows the probability of being treated, thus finding beneficiary individuals to the right and to the left of the threshold at each of the cut-off points. The results show that there are differences in labour market insertion between treated and untreated individuals, in favour of the former, but higher wages for non-beneficiaries. As for the estimates of the fuzzy regression regressions for both remuneration at the different points in time and labour market insertion, it is not possible to identify a positive impact of the treatment.
Keywords: C14; C21; C52; I22; 330; Educational funding; impact evaluation; fuzzy regressions; social mobility; higher education